Introduction of Medicinal Plants in The South of Lorestan Province - Mohammad Mehrnia; Zahra Hosseini (Shahrekord University of Medical Sciences, 2024)
Background and aims: The present study identified the medicinal species of southern Lorestan province and explored their traditional uses and potential applications in modern medicine. Methods: The study involved face-to-face interviews and personal observations to gather information on local names and traditional medicinal uses of plants. Use value (UV) and informant consensus factor (ICF) were used to analyze the data obtained from the interviews. The UV index was calculated to determine the relative importance of medicinal species native to the region. Results: The plant species were identified using standard herbarium methods. A total of 106 medicinal species from 95 genera and 40 plant families were identified, which are utilized by locals for various medicinal purposes in southern Lorestan province. According to the findings, leaves (22.3%), seeds (19%), and fruits (14.5 %) were the most commonly used parts of medicinal species. Edible and infusion were identified as the primary treatment methods in traditional medicine in southern Lorestan province. Conclusion: The predominant therapeutic uses of medicinal species in traditional medicine in the area focused on treating digestive disorders.